International Student in Japan - Warren, Kyle D.; Kim, Eunyoung (Journal of International Students, 2015)
Since 1983, the Japanese government has worked to implement various reforms to make higher education in Japan more attractive to international students (Horie, 2002). Verbik and Lasanowski (2007) have identified Japan as an “evolving destination” (p. 14) in international mobility with a growing number of international students choosing to study in Japan.